MODEL OF THE CATEGORY OF STATE AS “FUZZY MULTIPLICITY”: CATEGORICAL FOCUS OF QUALITATIVITY - Shapochkina, O. (Studia Philologica, 2020)
The research reconstructed the category of state in the old Germanic languages (Gothic, Old Saxon, Old Icelandic, Old English, Old High German) by structuring categorical focuses within the state paradigm. In the paper it is proposed to consider the category of state in the Old Germanic languages as “fuzzy multiplicity” where the nucleus is the predicate of state, and around it concentrates the state protocategorial construction with subject-object relations of physical, emotional-psychological, mental state and state of perception which transmit different macro-states within the state situation that contains such categorical focuses as quality, opposition, divergence, convergence and mobility. The article covers the essence of the categorical focus for qualitative state category in the Old Germanic languages. In particular, it was done comparison of quantitative indicators usage in state protocategorial constructions for active state, intertiv (inactive constructions), mediopassiv, constructions with IV-class verbs with ending –nan in Gothic, constructions with copula-verbs “to be/to become” + participle II, constructions with participle II, reflexive constructions, reciprocal constructions. Comparison was done in the Gothic-Scandinavian and West-Germanic language areas, and it is based on such Old Germanic literature sources as the Gothic Bible “Wulfila”, “Beowulf”, “Heliand”, “Song of Hildebrand”, “Muspilli”, “Song of Ludwig”, “Old Norse Edda”. The methods used in the study revealed the fundamental development actualisers and similar and distinctive features of the category of state in the Old Germanic languages. The reconstruction of the category of state for the Old Germanic languages in modern aspect has been restored. The research represents new vision of existing truths and positive experience for re-thinking the given interpretations. Key words: category of state, Old Germanic languages, predicate of state, fuzzy multiplicity, state protocategorial construction, model of state category in Old Germanic languages.